Corruption Reduction in Nigerian: Appraisal of the Role of Music - Ogunrinade, D. O. A. (Richtmann Publishing, 2013)
Corruption, also known as dishonesty has been the major hindrance to the development of a nation. The resultant effect of thisdeceit to any country is backwardness and underdevelopment. The root of corruption grows from the heart of a dissatisfiedperson. Such an individual does not find happiness from within and thus hankers for fulfillment in wealth, power and fame. Heis hungry spiritually, so he gets his temporary pleasures from the world. It is a deep problem that can only be purged bystrength more superior than political power. Music as one of the most common means by which man expresses his emotions,feelings and sentiments has the ability and the power to shape and reshape the character of human beings since it performsinnumerable functions from birth through adolescence to adulthood and at death in African setting. Similarly, it plays importantroles in daily activities of man and its relevance in curbing social vices in the society cannot be over emphasized sincecorruption is a behavioural pattern than ordinary occurrence. An effort is made in this article to examine the concept ofcorruption, its effect on the nation economy, Music attributes to humanity and its roles to control this social device calleddishonesty are the key motivator for this paper.